Cytometry by time of flight identifies distinct signatures in patients with systemic sclerosis, systemic lupus erythematosus and Sjögrens syndrome. Issue 1 (11th September 2019) - van der Kroef, Maarten; van den Hoogen, Lucas L.; Mertens, Jorre S.; Blokland, Sofie L.M.; Haskett, Scott; Devaprasad, Abhinandan; Carvalheiro, Tiago; Chouri, Eleni; Vazirpanah, Nadia; Cossu, Marta; Wichers, Catherina G.K; Silva‐Cardoso, Sandra C.; et al.
Abstract: Systemic sclerosis (SSc), systemic lupus erythematosus (SLE) and primary Sjögrens syndrome (pSS) are clinically distinct systemic autoimmune diseases (SADs) that share molecular pathways. We quantified the frequency of circulating immune‐cells in 169 patients with these SADs and 44 healty controls (HC) using mass‐cytometry and assessed the diagnostic value of these results. Alterations in the frequency of immune‐cell subsets were present in all SADs compared to HC. Most alterations, including a decrease of CD56 hi NK‐cells in SSc and IgM + Bcells in pSS, were disease specific; only a reduced frequency of plasmacytoid dendritic cells was common between all SADs Strikingly, hierarchical clustering of SSc patients identified 4 clusters associated with different clinical phenotypes, and 9 of the 12 cell subset‐alterations in SSc were also present during the preclinical‐phase of the disease. Additionally, we found a strong association between the use of prednisone and alterations in B‐cell subsets. Although differences in immune‐cell frequencies between these SADs are apparent, the discriminative value thereof is too low for diagnostic purposes. Within each disease, mass cytometry analyses revealed distinct patterns between endophenotypes. Given the lack of tools enabling early diagnosis of SSc, our results justify further research into the value of cellular phenotyping as a diagnostic aid. Abstract : Employing cytometry by time‐of‐flight we identified the frequency of 44 circulating immune cell subsets in 169 patients with autoimmune disorders and 44 healthy controls. Shared and unique circulating immune cell signatures associated to clinical phenotypes are observed in patients with SSc, SLE and pSS.